Quality of Life and a Surveillant Endocannabinoid System - de Melo Reis, Ricardo Augusto; Isaac, Alinny Rosendo; Freitas, Hércules Rezende; de Almeida, Mariana Macedo; Schuck, Patricia Fernanda; Ferreira, Gustavo Costa; Andrade-da-Costa, Belmira Lara da Silveira; Trevenzoli, Isis Hara (Frontiers in Neuroscience, 2021)
The endocannabinoid system (ECS) is an important brain modulatory network. ECS regulates brain homeostasis throughout development, from progenitor fate decision to neuro- and gliogenesis, synaptogenesis, brain plasticity and circuit repair, up to learning, memory, fear, protection, and death. It is a major player in the hypothalamic-peripheral nerve system-adipose tissue in the regulation of food intake, energy storage, nutritional status, and adipose tissue mass, consequently affecting obesity. Loss of ECS control might affect mood disorders (anxiety, hyperactivity, psychosis, depression), lead to drug abuse, and impact neurodegenerative (Alzheimer’s, Parkinson, Huntington, Multiple and Amyotrophic Lateral Sclerosis) and neurodevelopmental (autism spectrum) disorders. Practice of regular physical and/or mind-body mindfulness and meditative activities have been shown to modulate endocannabinoid (eCB) levels, in addition to other players as brain-derived neurotrophic factor (BDNF). ECS is involved in pain, inflammation, metabolic and cardiovascular dysfunctions, general immune responses (asthma, allergy, arthritis) and tumor expansion, both/either in the brain and/or in the periphery. The reason for such a vast impact is the fact that arachidonic acid, a precursor of eCBs, is present in every membrane cell of the body and on demand eCBs synthesis is regulated by electrical activity and calcium shifts. Novel lipid (lipoxins and resolvins) or peptide (hemopressin) players of the ECS also operate as regulators of physiological allostasis. Indeed, the presence of cannabinoid receptors in intracellular organelles as mitochondria or lysosomes, or in nuclear targets as PPAR might impact energy consumption, metabolism and cell death. To live a better life implies in a vigilant ECS, through healthy diet selection (based on a balanced omega-3 and 6 polyunsaturated fatty acids), weekly exercises and meditation therapy, all of which regulating eCBs levels, surrounded by a constructive social network. Cannabidiol, a diet supplement has been a major player with anti-inflammatory, anxiolytic, antidepressant and antioxidant activities. Cognitive challenges and emotional intelligence might strengthen the ECS, which is built on a variety of synapses that modify human behavior. As therapeutically concerned, the ECS is essential for maintaining homeostasis and cannabinoids are promising tools to control innumerous targets.